Wpływ stopnia formalizacji działań na innowacyjność przedsiębiorstwa - Hopej-Kamińska, Magdalena; Hopej, Marian; Kamiński, Robert (The influence of actions formalization degree on the innovation of an enterprise, 2006)
Formalization of organizational structure - one of the most frequent causes of innovation factor was stated. Research hypotheses were presented, that define the influence of formalization on the innovation in an enterprise. The applied research method was described and the hypotheses were verified.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 354-361